Luminescent Monitoring of Eu³⁺-Doped 13-93 Bioactive Glass Fiber Degradation - Baranowska, Agata; Markowski, Krzysztof; Zgłobicka, Izabela; Łępicka, Magdalena; Miluski, Piotr; Kochanowicz, Marcin (Photonics Letters of Poland, 2025)
Bioactive 13-93 glass fibers were doped with 0.2 and 2% mol of Eu3+ ions, and drawn using a traditional method. The study examined the degradation rate using the proposed optical method and to analyze the influence of the dopant on the degradation process. The fibers were immersed in SBF for 48 hours, with simultaneous and continuous measurement of the change in the luminescence spectrum (λexc.= 394 nm) at 611 nm. The morphology of the fibers was also investigated. Optical time constant analysis demonstrated that bioactive glass fibers doped with 2% moles of Eu3+ decomposed more slowly than 13-93_02Eu. Full Text: PDF References L.L. Hench, R.J. Splinter, W.C. Allen, and T.K. Greenlee, "Bonding mechanisms at the interface of ceramic prosthetic materials," J. Biomed. Mater. Res., 5(6), 117 (1971). CrossRef M. Brink, T. Turunen, R.-P. Happonen, and A. Yli-Urpo, "Compositional dependence of bioactivity of glasses in the system Na2O-K2O-MgO-CaO-B2O3-P2O5-SiO2," J. Biomed. Mater. Res., 37(1), 114 (1997). CrossRef Y.-H. Chan et al., "An evaluation of the biocompatibility and osseointegration of novel glass fiber reinforced composite implants: In vitro and in vivo studies," Dent. Mater., 34(3), 470 (2018). CrossRef M.T. Souza, S. Tansaz, E.D. Zanotto, and A.R. Boccaccini, "Bioactive Glass Fiber-Reinforced PGS Matrix Composites for Cartilage Regeneration," Materials (Basel)., 10(1) 2017. CrossRef C.R. Patra et al., "In vivo toxicity studies of europium hydroxide nanorods in mice," Toxicol. Appl. Pharmacol., 240(1), 88 (2009). CrossRef M. Shi et al., "Europium-doped mesoporous silica nanosphere as an immune-modulating osteogenesis/angiogenesis agent," Biomaterials, 144,176 (2017). CrossRef C.R. Patra et al., "Pro-angiogenic Properties of Europium(III) Hydroxide Nanorods," Adv. Mater., 20(4), 753 (2008). CrossRef A. Baranowska et al., "Luminescence Sensing Method for Degradation Analysis of Bioactive Glass Fibers," Sensors , 21(6) (2021). CrossRef T. Kokubo and H. Takadama, "How useful is SBF in predicting in vivo bone bioactivity?," Biomaterials, 27(15), 2907 (2006). CrossRef